Analysis of Delegation Leadership and Paternalistic Leadership on Organizational Development Mediated by Organizational Culture - Nuraeni, Nuraeni; Yuntina, Lily; Tri Hari Safariningsih, Ratna; Untari, Dewi; Supardi, Supardi (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on the analysis of delegation leadership and paternalistic leadership on organizational development mediated by organizational culture is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Delegation Leadership influences Organizational Culture; 2) Paternalistic Leadership influences Organizational Culture; 3) Delegation Leadership influences Organizational Development; 4) Paternalistic Leadership influences Organizational Development; 5) Organizational Culture influences Organizational Development; 6) Delegation Leadership influences Organizational Development through Organizational Culture; and 7) Paternalistic Leadership influences Organizational Development through Organizational Culture.